2015
DOI: 10.1007/s11618-015-0648-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of reading trainings on reading processes: a comparison in Grade 2

Abstract: Phonics, fluency, and reading strategy trainings are evidence-based interventions that foster the reading skills of poor readers in primary school. The purpose of the present study was to compare differential effects of the three types of trainings on the efficiency of component processes on word, sentence, and text level immediately after the training and at a 3-month follow-up. The 235 poor readers were randomly allocated to one of the reading interventions or to a control condition. All 490 B. Müller et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The EffectLiteR approach has been successfully applied to analyze average and conditional effects in various substantive examples especially from clinical psychology and educational science. For example, it has been used to estimate the effects of an autonomy-supportive intervention for teaching physics lessons in high school (Flunger, Mayer, & Umbach, 2018; Mayer, Umbach, Flunger, & Kelava, 2017), for analyzing the effects of inpatient psychotherapy on attachment characteristics (Kirchmann et al, 2011), for examining early transition to secondary school compared to late transition (Mayer, Nagengast, Fletcher, & Steyer, 2014), for evaluating a stress prevention program with teacher students (Karing & Beelmann, 2016), and for looking at differential effects of reading trainings on reading processes (Müller et al, 2015). Most of these examples include either latent covariates or latent outcome variables in the statistical model.…”
Section: Models For Causal Effectsmentioning
confidence: 99%
“…The EffectLiteR approach has been successfully applied to analyze average and conditional effects in various substantive examples especially from clinical psychology and educational science. For example, it has been used to estimate the effects of an autonomy-supportive intervention for teaching physics lessons in high school (Flunger, Mayer, & Umbach, 2018; Mayer, Umbach, Flunger, & Kelava, 2017), for analyzing the effects of inpatient psychotherapy on attachment characteristics (Kirchmann et al, 2011), for examining early transition to secondary school compared to late transition (Mayer, Nagengast, Fletcher, & Steyer, 2014), for evaluating a stress prevention program with teacher students (Karing & Beelmann, 2016), and for looking at differential effects of reading trainings on reading processes (Müller et al, 2015). Most of these examples include either latent covariates or latent outcome variables in the statistical model.…”
Section: Models For Causal Effectsmentioning
confidence: 99%
“…Teacher instruction not only improves reading comprehension ability but also helps promote reading self‐regulation (de Corte, Verschaffel, & van de Ven, ; McKeown et al, ; Oakhill & Cain, ; Pressley, ; Spörer & Schünemann, ; Spörer et al, ; van Keer, ). Even so, some fundamental issues about reading strategy instruction have been inconclusive and need further study, such as the types and frequency of strategies taught in reading lessons, the best time for students to internalize these strategies (Duke & Pearson, ; Ness, ; Sonnenschein, Stapleton, & Benson, ), and student age groups (upper primary grades or lower grades) for achieving optimal effects (Müller et al, ). As these issues are related to pedagogical approaches that may benefit primary‐school students struggling with reading comprehension (Hartman, ), we addressed some of the research gaps by using a large‐scale assessment database of Hong Kong students, in a high reading achieving region, to understand how student achievement is influenced by instructional practices and motivational factors.…”
Section: Introductionmentioning
confidence: 99%
“…These interventions explicitly target on higher-order skills of integration and comprehension and waive teaching phonem-code strategies. Nevertheless, some studies have also found positive side-effects on accuracy and fluency of word reading ( Suggate, 2014 ; Potocki et al, 2015 ; for effects on fluency, see Müller et al, 2015a ).…”
Section: Introductionmentioning
confidence: 99%